High street : how our town centres can bounce back from the retail crisis - Rudlin, David; Payne, Vicky; Montague, Lucy (London : Riba Publishing, 2023)
The high street is in crisis. How did we get here and what happens next? The global pandemic has made the crisis immeasurably worse but it wasn't the cause. The crisis was already raging in 2019 with thousands of store closures. Large retailers became complacent and failed to respond to changing consumer behaviour.
Chapter 13 The Mall -- Chapter 14 The Town -- Chapter 15 The High Street -- Chapter 16 Conclusions: New Life for Town Centres -- Notes -- Index -- Image Credits
Keywords: Retail trade -- Great Britain; Stores, Retail -- Great Britain; ARCHITECTURE / Urban & Land Use Planning; ARCHITECTURE / General